The Struggle for the Past How We Construct Social Memories - Jelin, Elizabeth (Berghahn Books, 2021)
In all societies-but especially those that have endured political violence-the past is a shifting and contested terrain, never fixed and always intertwined with present-day cultural and political circumstances. Organized around the Argentine experience since the 1970s within the broader context of the Southern Cone and international developments, The Struggle for the Past undertakes an innovative exploration of memory's dynamic social character. In addition to its analysis of how human rights movements have inflected public memory and democratization, it gives an illuminating account of the emergence and development of Memory Studies as a field of inquiry, lucidly recounting the author's own intellectual and personal journey during these decades
Description based on online resource; title from PDF title page (publisher's Web site, viewed 04. Okt 2022)
Keywords: HISTORY / Historiography; Collective memory -- Argentina; Human rights -- Argentina; Memorialization -- Argentina; State-sponsored terrorism -- 20th century -- Argentina; State-sponsored terrorism -- Argentina -- 20th century